Health related quality of life in endometriosis: Associated with depression, anxiety and stress, and predicted by psychological flexibility - Strobl, Elena; Lohse, Johanna; Schubert, Kathrin; Weise, Cornelia (3. Deutscher Psychotherapiekongress, 2024)
Background. Endometriosis is one of the most common gynaecological diseases, yet affected women remain in the shadow s for years before they receive a diagnosis and care. The negative impact of endometriosis on health-related quality of life is well established. Patients with endometriosis are often found to be suffering from depressive symptoms as well as anxiety. However, little is known about how endometriosis relates to other psychological constructs and disorders. Furthermore, stage of the disease and endometriosis related quality of life (E-QoL) are often unrelated which raises questions as to what predicts E-QoL. Our aim was to shed light on the associations between E-QoL and other psychological constructs and individual characteristics in order to gain a better understanding of how endometriosis affects health related quality of life. Methods. As part of a longitudinal study, 330 completed a first survey including an assessment of E-QoL (i.e. the Endometriosis Health Profile, EHP), the Beck Depression Inventory (BDI) and the Web-based screening questionnaire (WSQ). Of those, 164 completed a second survey including the EHP as well as the Pain Disability Index (PDI), Patient Health Questionnaire-9 (PHQ-9), the Perceived Stress Scale-10 (PSS-10), the Big Five Inventory (BFI) and the Acceptance and Action Questionnaire-II (AAQ-II). Results. In the first survey, lower E-QoL (higher EHP score) was significantly associated with depressive symptoms in the BDI (r=.62, p<.05) and the WSQ (r=.45, p<.05) as well as with symptoms of generalised anxiety disorder in the WSQ (r=.43, p<.0). In the second survey low E-QoL was significantly associated with depressive symptoms (PHQ-9; r=.60, p<.05) and higher perceived stress (PSS-10; r=.55, p<.05). A multiple linear regression model indicated that the Big Five personality traits predicted E-QoL (EHP score) (F(5, 158)=2.68, p<.05, R²=.049), where conscientiousness was a negative (t=-2.36, p<.05) and neuroticism a positive predictor (t=2.78, p<.01). However, when adding AAQ-II as a predictor to the model (F(6, 157)=20, p<.001, R²=.411), AAQ-II remained the only significant predictor (t=9.91, p<.001). Neither age nor time since diagnosis were found to be significant predictors of endometriosis related quality of life . Conclusion. A low endometriosis-related quality of life relates to depressive mood, anxiety and stress. While directionality of these relationships cannot be concluded by our data, the relationships highlight that E-QoL may be improved by interventions focusing on stress as well as mood regulation. While personality traits may affect E-QoL to a small degree, psychological flexibility as measured by the AAQ-II appears more relevant. Psychological flexibility may serve as a protective factor to endometriosis related quality of life. Keywords: Endometriosis, Quality of Life, Women’s Heal